Phonology : a coursebook - Kennedy, Robert, 1974- (Cambridge University Press, 2017)
This practical and accessibly written textbook provides a thoughtfully ordered introduction to a wide range of phonological phenomena. It contains many exercises combining classic datasets with newly compiled problems. These help the student learn to discover sound patterns nested in complex linguistic data, beginning with concrete introductory examples and stepping through a series of progressively more complex phonological phenomena. It covers alternation, vowel harmony, phonemic analysis, natural classes and distinctive features, abstractness and opacity, syllable structure, tone, stress, prosodic morphology, feature geometry, and optimality theory. It is essential reading for students of linguistics around the world.